AN EXPERIMENTAL STUDY ON MECHANICAL BEHAVIOUR OF CONCRETE USING RECYCLED CONCRETE AGGREGATES - Lal, Prof. Roshan; Singla, Er. Sarita; Kumar, Er. Kuldeep; Singh, Er. Apinderjit (IJRDO - Journal of Mechanical And Civil Engineering, 2015)
The paper deals with restriction the use of natural aggregates in concrete and is concerned with selecting recycled aggregates for concrete to sustainable development by restricting the use of natural resources. An estimated 25 billion tonnes of concrete is manufactured globally every year in the US, Japan and Europe of which approximately 900 million tonnes of construction and demolition waste is generated yearly. In India, the total quantum of (C&D) waste is estimated to be 12 to 14.7 million tons per annum.The paper reveals studies carried out to obtain recycled aggregates from construction and demolition waste and its use in concrete construction. The paper also explores the feasibility of replacing fine aggregates by fly ash. It is demonstrated that recycled aggregates upto some percentage of replacement with natural aggregates can be used to effectively match the performance of conventional concrete.